1998
DOI: 10.2138/am-1998-11-1228
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite from magnetotactic bacteria; size distributions and twinning

Abstract: We studied intracellular magnetite particles produced by several morphological types of magnetotactic bacteria including the spirillar (helical) freshwater species, Magnetospirillum magnetotacticum, and four incompletely characterized marine strains: MV-1, a curved rodshaped bacterium; MC-1 and MC-2, two coccoid (spherical) microorganisms; and MV-4, a spirillum. Particle morphologies, size distributions, and structural features were examined using conventional and high-resolution transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(116 citation statements)
references
References 34 publications
9
107
0
Order By: Relevance
“…4 yield a mean plane separation of 43.1 ± 4.5 nm, with a center-to-center spacing of 56.8 ± 3.7 nm (1σ errors); the average interparticle gap of ~ 13.7 ± 2.1 nm is consistent with two unit membranes. This size distribution is in good agreement with the measurements of Devourd et al [39], who also did not use negative staining but had no 3-dimentional control of the chain warping. Our measured interparticle spacing, however, is significantly larger than the 10.0 nm (2 x 5.0 nm) spacing reported by Gorby et al [1], which may be a result of the negative staining procedure enhancing the apparent size of the crystals.…”
Section: 2supporting
confidence: 91%
See 1 more Smart Citation
“…4 yield a mean plane separation of 43.1 ± 4.5 nm, with a center-to-center spacing of 56.8 ± 3.7 nm (1σ errors); the average interparticle gap of ~ 13.7 ± 2.1 nm is consistent with two unit membranes. This size distribution is in good agreement with the measurements of Devourd et al [39], who also did not use negative staining but had no 3-dimentional control of the chain warping. Our measured interparticle spacing, however, is significantly larger than the 10.0 nm (2 x 5.0 nm) spacing reported by Gorby et al [1], which may be a result of the negative staining procedure enhancing the apparent size of the crystals.…”
Section: 2supporting
confidence: 91%
“…3 and 5 as regular truncated octahedra ('cubooctahedra' using the terminology of [39]), and the sheath as a simple cylinder surrounding the magnetosome chain. In the magnetospirilla, numerous studies have shown that the crystals tend to be aligned with their crystal axes parallel to the [111] cubic direction (i.e., they have parallel sets of {111} crystal faces perpendicular to the chain axis).…”
Section: 2mentioning
confidence: 99%
“…Crystallographic Perfection Electron microscopy studies reveal that MTB magnetite crystals are essentially free of inner defects, with minor exceptions of {111} twinnings (Devouard et al, 1998). The crystallographic lattice lack of defects contributes to enhance the particle net magnetic moment.…”
Section: Chemical Puritymentioning
confidence: 99%
“…and observed that not only were the magnetite crystals produced by these magnetotactic bacteria of a much narrower size distribution than their abiotic cousins, they also exhibited an asymmetry in size distribution that is not observed in synthetic samples. 20 TEM analysis of magnetosomes synthesized by magnetotactic bacterium MC-1 has revealed that control over crystal structure occurs at a very early stage of crystal growth, and the medium of the culture impacts both the morphology and number of magnetite crystals, with an acetate-containing medium yielding more crystals than a sulfi de-containing medium. Such exquisite control over magnetite structure is of extreme relevance in many applications, including the development of nanotechnologybased therapeutics.…”
Section: Magnetosomesmentioning
confidence: 99%